How do patients and General Practitioners talk about pain and negotiate empathy in consultations? A direct observational study. (4th January 2021) - Thompson, Lee; Dowell, Anthony; Hilder, Jo; Macdonald, Lindsay; Stubbe, Maria; Alchin, John
Abstract: The objective of this qualitative study in New Zealand was to investigate how general practitioners and patients discuss chronic pain in consultations. Chronic pain is a complex condition that defies many commonsense understandings. It is challenging to manage and patients can come to conclude that there is an empathy deficit. To our knowledge most, if not all, studies on this topic have recruited participants whose main presenting complaint is chronic pain. Forms of chronic pain are relatively common in the population and we thought it likely that at least some discussions may be rendered invisible via these recruiting practices. The study analysed data from the Applied Research on Communication in Health repository of audio transcripts and video‐recorded consultations collected from a range of studies on a variety of topics, none of which were about chronic pain specifically. We searched the 256 transcripts looking for key words that might indicate that pain was at least part of the consultation. This yielded a large number of potentially relevant transcripts. These transcripts were assessed and reduced to 18 by excluding those that were about non‐physical pain or pain that was expected to resolve relatively quickly. A medical specialist in chronic pain reviewed the resulting 18 and excluded two further transcripts giving us a final sample of 16. We conducted in‐depth analysis of these consultations. Rather than confirming an empathy deficit, we found a much more complex deployment of empathy in the space where the two complex systems of chronic pain and general practice meet. These findings highlight the utility of analysing data originally generated for other purposes, with permission, and in a practical sense, highlight the importance of understanding empathy as highly contextual in 'real world' practice.